C-terminal of ABCA1 separately regulates cholesterol floppase activity and cholesterol efflux activity. Issue 4 (2nd April 2020) - Okamoto, Yusuke; Tomioka, Maiko; Ogasawara, Fumihiko; Nagaiwa, Kota; Kimura, Yasuhisa; Kioka, Noriyuki; Ueda, Kazumitsu
ABSTRACT: ATP-Binding Cassette A1 (ABCA1) is a key lipid transporter for cholesterol homeostasis. We recently reported that ABCA1 not only exports excess cholesterol in an apoA-I dependent manner, but that it also flops cholesterol from the inner to the outer leaflet of the plasma membrane. However, the relationship between these two activities of ABCA1 is still unclear. In this study, we analyzed the subcellular localization of ABCA1 by using a newly generated monoclonal antibody against its extracellular domain and the functions of eleven chimera proteins, in which the C-terminal domain of ABCA1 was replaced with those of the other ABCA subfamily members. We identified two motifs important for the functions of ABCA1. Three periodically repeated leucine residues were necessary for the cholesterol floppase activity but not the cholesterol efflux activity, while a VFVNFA motif was essential for both activities of ABCA1. These results suggest that the C-terminal of ABCA1 separately regulates the cholesterol floppase activity and the cholesterol efflux activity. Graphical abstract: : The three leucine residues and the VFVNFA motif in the C-terminal of ABCA1 separately regulate cholesterol efflux and floppase activity.